2013
DOI: 10.1016/j.ajhg.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Small Exonic CNV from Whole-Exome Sequence Data and Application to Autism Spectrum Disorder

Abstract: Copy number variation (CNV) is an important determinant of human diversity and plays important roles in susceptibility to disease. Most studies of CNV carried out to date have made use of chromosome microarray and have had a lower size limit for detection of about 30 kilobases (kb). With the emergence of whole-exome sequencing studies, we asked whether such data could be used to reliably call rare exonic CNV in the size range of 1-30 kilobases (kb), making use of the eXome Hidden Markov Model (XHMM) program. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
122
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(128 citation statements)
references
References 47 publications
1
122
0
5
Order By: Relevance
“…Cut-offs for CNV calling were also set at a minimum coverage of three markers/ probes per CNV, restricting downstream genetic and functional analyses to variants exceeding these minimum size thresholds. While more difficult to detect reliably by microarray approaches, small exonic CNVs of 1-30 kb have been suggested to contribute to susceptibility of some genetic diseases [71]. Finally, analyses were restricted to CNVs involving coding regions of at least one gene, ignoring variants solely impacting intronic or regulatory sequences.…”
Section: (D) Study Limitationsmentioning
confidence: 99%
“…Cut-offs for CNV calling were also set at a minimum coverage of three markers/ probes per CNV, restricting downstream genetic and functional analyses to variants exceeding these minimum size thresholds. While more difficult to detect reliably by microarray approaches, small exonic CNVs of 1-30 kb have been suggested to contribute to susceptibility of some genetic diseases [71]. Finally, analyses were restricted to CNVs involving coding regions of at least one gene, ignoring variants solely impacting intronic or regulatory sequences.…”
Section: (D) Study Limitationsmentioning
confidence: 99%
“…Further studies found an enrichment of genes involved in MAPK signaling and neuronal development in autismassociated deletions [189]. Also, analysis of CNVs identified from WES data found an enrichment of cytoskeletal and autophagy genes in small CNVs in autism [190].…”
Section: Autism Genetic Studies May Point To Convergentmentioning
confidence: 88%
“…[34][35][36][37] Meanwhile, genome-wide and microarray-based comparative genomic hybridizations have found that the CNV burden is also increased in patients with schizophrenia or autism-spectrum disorders compared with healthy controls. [38][39][40][41] For example, microduplications of 1q21.1 or 16p11.2 and deletions at 2p16.3, 15q11.2 or 22q11.21 have been reported in patients with schizophrenia and autism-spectrum disorders. 42 De novo gene-disrupting SNVs have also been found to occur at higher rates in patients with autismspectrum disorders than in controls.…”
Section: J Psychiatry Neurosci 2018;43(4)mentioning
confidence: 99%